Development of Humanistic Statistics Learning Devices Based one Inquiry and Mind Mapping Models - Pramesti, Santika Lya Diah; Salafudin, Salafudin (Universitas Islam Raden Intan Lampung, INDONESIA, 2018)
The purpose of this research are: (1) to determine the characteristic of humanistic statistics learning, (2) to obtain a humanistic statistics learning tools based on valid, practical, and effective inquiry and mind mapping learning model. The research method uses 4D Thiagarajan which has been modified to 3D, namely: define, design, and develop. Implementation of the development and humanistic statistics learning tool trials using Inquiry and Mind Mapping learning model show that learning tools used in statistical learning activities were practical and effective. The trial shows an increase of students’ statistical problem-solving ability using humanistic learning based on Inquiry and Mind Mapping learning model. The improvement of statistical problem-solving on Inquiry learning model is better than humanistic statistics learning using Mind Mapping learning model.